Developing E-Book Based on Multimodal Digital Storytelling Approach to Enhance the Seventh Grade Students’ English Skills - Amelia, Pratiwi; Handayani, Rindu; Pratama, Suprayuandi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Despite the widespread research on the use of technology and multimodal digital storytelling to boost the students ‘learning, there are only fewer studies conducted in junior school circumstances. To fill this gap, this study aims to develop e-book based on multimodal digital storytelling and local wisdom to enhance the seventh-grade students’ English skills. The framework of technological, pedagogical, content and technological knowledge (TPACK) adopted as the theoretical background in this study. Research and development (R&D) method through ADDIE model was employed to construct e-book based on the seventh-grade students’ needs in learning language in which consist of five stages namely Analysis, Design, Development, Implementation, Evaluation. The findings showed that e-book based on multimodal digital storytelling approach able to create interactive activities to improve the students’ competencies in generating ideas, igniting creativity, and developing multimodal literacy. The findings also reveal that multimodal digital storytelling approach adopted are applicable to junior school students to improve their motivation in learning language.